Teknologi Pengolahan Minuman Rempah Instan Sebagai Peluang Usaha Serta Meningkatkan Daya Tahan Tubuh Terhadap Covid 19 - Maria Isfus Senjawati; Maryam Maryam; Fera Afriyuni (Journal of Appropriate Technology for Community Services, 2021)
We are currently faced with the problem of the Covid 19 pandemic and no cure has been found. One of the efforts made by the community is to implement health protocols to the recommendations from the government and increase the body's resistance to prevent this Covid 19 attack. Indonesia has a wealth of spices that are quite large in number and type. According to some studies that this spice can increase the body's resistance because it contains antioxidants and active compounds that can ward off free radicals. This is one of the business opportunities as well as an effort to increase the body's endurance if consumed. Community service activities organized by ATI Padang Polytechnic, Agro Industry Engineering Study Program aims to provide technology for processing instant spice drinks based on red ginger. The spices used are red ginger, cinnamon, cloves and lemongrass. The product produced is instant red ginger. Partners of this activity are UKM/communities in Bungo Pasang Subdistrict, Koto Tangah District, Padang. The method used is to deliver processing technology through virtual training and practice independently. After attending virtual training and independent practice using equipment and materials that have been assisted by team, participants submitted their products that have been packaged as evaluation materials. It is hoped that with this activity, UKM/communities can produce this product in order to increase the resilience of the family as well as their business choice. The processing of spices into instant beverage products is expected to be widely marketed, more durable and provide added value to spice commodities. Kata kunci : Minuman instan, rempah, daya tahan tubuh